A guide to the ICC rules of arbitration - Derains, Yves (Kluwer Law International The HagueNL, 2005)
Provides article-by-article commentary on the ICC rules, expanded references in respect to the rules' individual provisions, and also references to relevant national court judgements and arbitral awards.